La gestion de l'incertitude dans une organisation internationale : le cas de I'OACI - Le Scouarnec, François-Pierre (Études internationales, 1996)
A typology of uncertainty reveals three dimensions: probability, vagueness, and ambiguity. At the International Civil Aviation Organization (ICAO), terrorism has appeared as a threat to the agency's mandate, which is to ensure the harmonious development of civil air transportation. Faced with the probability that a terrorist act may occur, decision-makers in the international civil aviation System have developed an array of institutional responses. In the area of law, several instruments were created as the impact of events and techniques used by terrorists developed. In the area of management, the ICAO created a special unit reporting directly to the Secretary General and reviewed technical standards and procedures for aviation personnel. While new technologies were being deployed to reduce the probability of an illicit act, political responses were elaborated : use of the UN Secretary-Generalship, politicization of the ICAO Council, and international cooperation in the fight against terrorism. Uncertainty can be a vector of organizational development. Perception of uncertainty and the actions it brings about belong to afield of analysis of interest to the school of epistemics.